2019
DOI: 10.1177/0954410019893215
|View full text |Cite
|
Sign up to set email alerts
|

Quaternion-based position control of a quadrotor unmanned aerial vehicle using robust nonlinear third-order sliding mode control with disturbance cancellation

Abstract: In this paper, we propose a robust nonlinear position and attitude control method for quadrotor using higher order sliding mode control concept. The control of quadrotor is realized in an inner- and outer-loop structure. Both inner- (attitude control) and outer (position control)-loop controllers are synthesized using third-order sliding mode control. The attitude control is designed in a quaternion framework to avoid gimbal lock and for better computational efficiency. A low-pass filter is used to reduce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…e following results can be observed from Figure 7: (1) e proposed LFSC method successfully forces attitude tracking errors (e ϕ , e θ , e ψ ) to converge to zero in finite time, while the SMC and fuzzy SMC methods force attitude tracking errors (e ϕ , e θ , e ψ ) to converge to small bounded fields around zero. (2) e performance of the proposed LFSC method was much better than that achieved by the SMC or fuzzy SMC method in terms of tracking accuracy and robustness. It could be seen that the timevariant disturbances were not well compensated with traditional SMC or fuzzy SMC method.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…e following results can be observed from Figure 7: (1) e proposed LFSC method successfully forces attitude tracking errors (e ϕ , e θ , e ψ ) to converge to zero in finite time, while the SMC and fuzzy SMC methods force attitude tracking errors (e ϕ , e θ , e ψ ) to converge to small bounded fields around zero. (2) e performance of the proposed LFSC method was much better than that achieved by the SMC or fuzzy SMC method in terms of tracking accuracy and robustness. It could be seen that the timevariant disturbances were not well compensated with traditional SMC or fuzzy SMC method.…”
Section: Resultsmentioning
confidence: 86%
“…e quadrotor, a typical unmanned aerial vehicle consisting of four symmetric propellers, has received much attention recently due to its low cost, easy maintenance, and potential for deployment in difficult environments [1]. e quadrotor design is the preferred choice for aerial robots, as quadrotor vehicles have vertical takeoff and landing capabilities and can hover at low speed [2]. As such, the quadrotor has been applied in many fields, including photography, education, transportation, and agriculture [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…For control design being amalgamated with observer or estimator, it is observed that dual loop SMC or higher order SMC is highly recommended for above case but here one should compromise either on settling time or steady state error. The higher order SMC addresses the issue in Sanwale et al 33 smartly but discussion of three unmodelled dynamic factors and exogenous disturbances in lumped form is not available. Simultaneously, POC-DE technique is limited to payload variation case only with bounded perturbations.…”
Section: Technical Analysis and Discussionmentioning
confidence: 99%
“…Third order Sliding mode control (TOSMC) 33 is used with quaternion approach to address the singularity problem and by using high order and low-pass filter for control signal the inherent issue of chattering is removed. The proposed technique is just designed for tackling the unmodelled factors and disturbances in general and no specific discussion is made regarding payload, wind disturbance and rotor efficiency loss.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The experimental and simulation results revealed the efficiency and strength of the designed control strategy in enhancing the reference tracking performance and disturbances rejection capability. In another similar study, Sanwale et al [94], proposed a robust non-linear position and attitude control methods based on a quaternion based third-order SMC paired with a low pass filter and disturbance observer for a quadcopter position control. The efficacy of the suggested controller was illustrated to reject continuous disturbances and model uncertainties with position accuracy up to a millimeter margin.…”
Section: Quad-rotor Systemsmentioning
confidence: 99%